2022
DOI: 10.3389/fnbeh.2022.941884
|View full text |Cite
|
Sign up to set email alerts
|

Early life maternal separation induces sex-specific antidepressant-like responses but has minimal effects on adult stress susceptibility in mice

Abstract: Early life stress is known to increase the risk of depression and anxiety disorders, which are highly prevalent conditions that disproportionately affect women. However, the results of preclinical studies have been mixed, with some work suggesting that early life stress promotes anxiety-like behavior and/or increases susceptibility to subsequent stressors, and other research suggesting that early life stress reduces anxiety-like behavior and/or confers resilience to subsequent stress exposure. It is likely tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Most of previous works conducted in C57Bl/6 exposed to MS report long-term effects on behaviour, only when animals were re-exposed to an additional stressor such as early weaning at PND17 (Tchenio et al, 2017), or chronic social defeat or UCMS at adulthood (Peña et al, 2017(Peña et al, , 2019. Without additional stress, emotional behaviours in MS C57Bl/6 mice generally did not significantly differ from controls (Millstein and Holmes, 2007;Tractenberg et al, 2016;Peña et al, 2017Peña et al, , 2019Baugher and Sachs, 2022;Shin et al, 2023). On the other hand, C3H/HeN strain used in the present study has been previously reported to induce gut dysfunction after MS (Riba et al, 2018;Ilchmann-Diounou et al, 2019;Rincel et al, 2019) and emotional impairments in a multi-hit model combining MS, maternal UCMS and prenatal infection (Rincel et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Most of previous works conducted in C57Bl/6 exposed to MS report long-term effects on behaviour, only when animals were re-exposed to an additional stressor such as early weaning at PND17 (Tchenio et al, 2017), or chronic social defeat or UCMS at adulthood (Peña et al, 2017(Peña et al, , 2019. Without additional stress, emotional behaviours in MS C57Bl/6 mice generally did not significantly differ from controls (Millstein and Holmes, 2007;Tractenberg et al, 2016;Peña et al, 2017Peña et al, , 2019Baugher and Sachs, 2022;Shin et al, 2023). On the other hand, C3H/HeN strain used in the present study has been previously reported to induce gut dysfunction after MS (Riba et al, 2018;Ilchmann-Diounou et al, 2019;Rincel et al, 2019) and emotional impairments in a multi-hit model combining MS, maternal UCMS and prenatal infection (Rincel et al, 2019).…”
Section: Discussionmentioning
confidence: 85%
“…Most of previous works conducted in C57Bl/6J exposed to MS report long-term effects on behavior, only when animals are re-exposed to an additional stressor such as early weaning at PND17 ( 48 ), chronic social defeat or unpredictable chronic mild stress (UCMS) at adulthood ( 25 , 26 ). Without additional stress, emotional behaviors in MS C57Bl/6J mice generally do not significantly differ from controls ( 25–27 , 43 , 49 , 50 ). On the other hand, C3H/HeN strain displays gut dysfunction after MS ( 17 , 30 , 31 ) and emotional impairments in a multi-hit model combining MS, maternal UCMS and prenatal infection ( 31 ).…”
Section: Discussionmentioning
confidence: 85%
“…Factors such as sex and the timing and severity of early-life and adult stress exposure seem to play a key role in determining whether a particular early-life experience would promote adaptive or maladaptive behavior later in life. Thus, researchers are now called to pay attention to individual differences that may impact different risk factors, the type of trauma, and the behavioral measures of symptoms before drawing conclusions [165][166][167][168][169]. These aspects are critical to be able to relate behavioral symptoms with their neural correlates and to establish effective drug development and drug testing platforms.…”
Section: What Are the Possible Barriers That May Limit Preclinical St...mentioning
confidence: 99%